Pediatric HEALTHCARE Provider Awareness, Confidence, and Use of Sports Specialization Recommendations and Application towards Youth Athlete Counseling. Issue 7 (30th July 2021) - McLeod, Tamara Valovich; Snedden, Traci; Post, Eric; Zaslow, Tracy; Fetchen-DiCesaro, Shelly; Mohrbacher, Denise; Bell, David; ,
Background: Sport specialization is increasingly common in many youth sports and has been linked to increased injury, overtraining, and burnout. Several organizations have developed safe sport recommendations in an effort to mitigate injury risk. Healthcare providers (HCPs) can be a source of education for parents and athletes on safe sports practices, but the awareness, confidence, and use of these recommendations among HCPs who work with youth athletes is limited.Hypothesis/Purpose: To evaluate the awareness, confidence, and use of sports specialization and safe sport recommendations of HCPs who work with pediatric athletes. Methods: A cross-sectional online survey was developed to assess pediatric HCP awareness of, confidence in, and clinical use of sports specialization recommendations. The survey included 1) personal demographics, 2) professional demographics, 3) knowledge and perceptions of sport specialization, 4) awareness, confidence, and use of recommendations, and 5) HCP program training and professional development background specific to sports specialization. Survey links were sent by email to 5000 secondary school athletic trainers and 297 PRiSM members during October 2019-January 2020. The survey was open for 4 weeks, with a reminder email sent after 2 weeks. Data was analyzed with descriptive statistics. Results: The survey was accessed by 620 HCPs (access rate=11.7%) and completed by 508 HCPs (completion rate=81.9%). Respondents (279 females, 228 males; age=37.2±10.5 years) included athletic trainers (74.5%, n=379), physicians (16.9%, n=86, physical therapists (6.7%, n=35), nurse practitioners (1.0%, n=5), and physician assistants (0.1%, n=4) with 11.2±9.1 years of experience providing care to pediatric athletes. Three-fourths of respondents (n=373) were aware of recommendations from the National Athletic Trainers' Association, but fewer were aware of those from the American Academic of Pediatrics (42.3%, n=212), American Medical Society for Sports Medicine (40.3%, n=200), American Orthopaedic Society for Sports Medicine (45.2%, n=225), International Olympic Committee (14.2%, n=69), Major League Baseball (30.6%, n=151), USA Hockey (13.6%, n=66), and National Basketball League (9.3%, n=45). The percentage of respondents who were confident in knowledge of (Table 1) and used (Table 2) each organization's recommendation are provided in the tables. Table 3 presents the degree to which various reasons limit the use of sports specialization recommendations. Conclusion: Healthcare providers are aware of sport specialization recommendations and believe they are associated with decreased risk of injury. However, barriers to applying the recommendations most cited were the inability of parents and children to change specialization behaviors. Future research should focus on implementation of recommendations to enact behavior change. Tables: